The Effect of Financial Literacy, Ease and Trust on the Decision to Use QRIS - Agustin, Kety Lulu; Usman, Wilma Widyanti; Kusno, Hendra Sanjaya (MEC-J (Management and Economics Journal), 2025)
This study aims to identify the influence of Financial Literacy, Ease of Use, and Trust on Transaction Decisions using QRIS at MSMEs in Balikpapan City. This research uses quantitative method with a sample of 400 MSMEs selected through Accidental sampling technique as part of Non-Probability Sampling. The results show that Financial Literacy, Ease of Use, and Trust simultaneously affect the Transaction Decision using QRIS. Partially, Financial Literacy and Ease of Use affect Transaction Decisions, indicating that increasing Financial Literacy and Ease of Use can encourage decisions to transact using QRIS. Conversely, Trust has no effect on Transaction Decisions using QRIS. This finding indicates that although Trust in the QRIS system does not affect transaction decisions, the Financial Literacy and Ease of Use factors still have an important role in MSME decisions to adopt QRIS as a payment method. This study provides valuable insights into the factors that need to be considered in increasing the adoption of QRIS among MSMEs in Balikpapan City. It is expected that further researchers add other relevant variables in order to get a deeper understanding of the adoption of QRIS by MSMEs.